DAMPAK PERUBAHAN KEBIJAKAN DAGANG STARBUCKS TERHADAP PEREKONOMIAN ETHIOPIA 2005-2008 - Fauziah, Ana; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains about how the the effect of the Starbucks policy trade changing to Ethiopian econnomy in 2005 until 2008. The purpose of this research is to know how the implementation of agreement between Ethiopian Government and Starbucks have effected to Ethiopia coffee industry. This case had been a conflict since 2004 when Ethiopian government knew their origin coffee was trademark by Strabucks in USPTO without their permission. Oxfam as Non-Government Organization that moved for justice make big campaign and pressure Starbucks to pulled up the coffee trademark in USPTO. In 2007, Starbucks had change their policy of trade about the trademark of Ethiopian coffee and reach agreement with Ethiopia government. This research is a qualitative research. Method applied in doing this research is description with aim to depict a phenomenon in this case. By using the neo-liberlism theory to analyze the role of non nation actor in a case and global value chain theory to analyze how every step in production chain will add value to the product it self.The result of this research shows The Starbucks policy trade changing gave positively effect to Ethiopian economy. Since the coffee trademark had been know in international coffee market as speciality coffee, many coffee trade agreement reached by Ethiopian and another corporation from another country. The result of agreement has improve positively to coffee volume and value export in international market and the welfare of Ethiopian coffee farmer. Keywords: Coffee Volume and Value, Ethiopia Economy Growth, Ethiophia Iniative and Licensing Trademark, Trademark, Trade Policy, Starbucks